FOOD WASTE IN MANHATTAN, KANSAS ELEMENTARY SCHOOL LUNCH - Schlechter, Chelsey R. (My University, 2015)
In the United States (US) 133 billion pounds of food was wasted at the consumer and retail level in 2010, resulting in a total loss of 161.6 billion dollars (Buzby, Wells, & Hyman, 2014). This translates into 387 billion calories per day being wasted, of which 96% ends up in landfills (Buzby et al., 2014). Moreover, decomposing food waste in landfills emits methane, a potent greenhouse gas, that accounts for 20% of all methane emissions (EPA, 2014). Food waste can come from a variety of sources, including at the farm level (e.g., food lost to a unfavorable environment conditions), the farm to retail level (e.g., foods that do not meet food safety regulations; are misshapen or blemished), the retail level (e.g., dented cans; damaged packaging), and the consumer level (e.g., plate waste; food that spoils before consumption) (Buzby et al., 2014). In 2013 the United States Department of Agriculture (USDA) and Environmental Protection Agency (EPA) launched the U.S Food Waste Challenge in an attempt to reduce, recover, and recycle food waste in the United States (USDA OCE, n.d.). One of the major commitments of the project was to minimize waste in school meal programs, where studies have shown plate waste to be 29-43% of food taken (Cohen, Richardson, Parker, Catalano, & Rimm, 2014).
Keywords: Food waste; School lunch; Public Health (0573)